DEVELOPMENT OF JUNIOR HIGH SCHOOL MATHEMATICS TEACHING MATERIALS ASSISTED BY GEOGEBRA SOFTWARE WITH A CONTEXTUAL APPROACH TO IMPROVE MATHEMATICAL CREATIVE THINKING: PENGEMBANGAN BAHAN AJAR MATEMATIKA SMP BERBANTUAN SOFTWARE GEOGEBRA DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PEMIKIRAN KREATIF MATEMATIS - Hikmal Setiawan; Nelly Fitriani; Jozua Sabandar (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to develop mathematics teaching materials assisted by geogebra media on the mathematical creative thinking abilities of seventh-grade students of junior high school. Implementation of teaching materials using geogebra-assisted media is a way to help students understand mathematics learning, especially in quadrilateral material. For the quality teaching materials to meet the criteria of being valid, practical, and effective. This research uses a type of research and development (R&D). In this research, a development model is used, namely the ADDIE model. The ADDIE model is a research and development model consisting of 5 (five) stages, namely analysis, design, development, implementation, and evaluation. The results obtained from this study are the validity of teaching materials that are declared very valid with teaching materials that have been developed using geogebra assistance produces valid and practical teaching materials for the learning process with the results of an average validity value of 96.93% and an average practicality value of 94.6%. Suggestions that can be given are to take advantage of the teaching materials that have been developed so that educators or students can take advantage of teaching materials carried out remotely online or offline. Then other researchers can develop this teaching material on other mathematics material so that it can be utilized by other audiences.